Investigation of mechanical properties of randomly distributed sisal fibre reinforced soil. (May 2014) - Wu, Y. K.; Li, Y. B.; Niu, B.
<x content-type="archive" xml:space="preserve">Abstract</x> Fibre reinforcement technology, which has been widely used in geotechnical engineering, such as, ground treatment, slope protection, retaining wall and so on, can effectively improve the bearing capacity and the shear strength of soil body. The present study is aimed at determining the behaviour of silty clay reinforced with sisal fibre in a random manner. The soil used is a type of silty clay which is representative in Qingdao District. The fibres are cut to different lengths (5, 10 and 15 mm) and mixed randomly with soil in varying percentages (0·5, 1·0 and 1·5%). The test results indicate an improvement in the strength, deformation and shear failure characteristics of soil due to the addition of sisal fibres. Additionally, the cohesion and the peak of the principal stress difference of the sisal fibre reinforced soil are improved to some extent compared with the plain soil.